P21 Comforting touch at home. (1st October 2013) - Williams, Sue; Birch, Helen; McDonald, Bernadette
Abstract : Aims: Hospice at Home service works with other community services to fill gaps in end of life care for patients, whose preferred place of care is home. A twenty four hour / seven days a week sitting service is delivered predominantly by trained Healthcare Assistants (Aides), who recognised that anxiety and breathlessness might benefit from immediate, simple non pharmacological interventions. Methods: Similar interventions are provided by appointment at the hospice and the Hospice at Home team were trained in simple skills and techniques (basic hand and foot massage, the importance of touch, and anxiety and breathlessness management). Regardless of the severity of condition, touch can always be safely administered and studies show massage as the second most commonly administered non-drug strategy to reduce symptoms. Hospice at Home Aides were encouraged to use these skills and techniques with patients, and teach them to families and informal carers where appropriate. Results: We present audit and survey results of this positive partnership between hospice, Aides, complementary therapists, families and community services. Conclusion: Families described better outcomes, empowered by doing something practical instead of feeling inadequate and helpless. Patients' symptoms were relieved immediately in the home instead of waiting to attend the Hospice, and confidence levels and job satisfaction increased amongst the Hospice at Home staff because they could respond immediately by providing a non-pharmacological technique for these distressing symptoms in the patient's place of choice - home. A cost effective, one stop shop!